FAKTOR-FAKTOR YANG DIPERTIMBANGKAN MASYARAKAT BERKUNJUNG PADA LOKASI WISATA KULINER KAMPUNG KAILI - Astin, Astin (Fakultas Ekonomi Universitas Tadulako, 2017)
The purpose of this study is to find out what factors are considered by the community to visit the culinary tourism locations of Kaili Village. This type of explorative research, namely research conducted because this research tries to explore information or problems that are relatively new. In this study researchers used a sample of 80 respondents. The sampling technique used in this study is accidental sampling. Data analysis method used in this study uses factor analysis. The results of this study indicate that there are 4 (four) factors that are considered by the community to visit the culinary tourism sites of Kaili Village. The four factors are, core service factors, menu factors, place factors, and unplanned needs factors which are the results of 16 variables analyzed.